Relationship between Peripheral Blood miR-181c, miR-101, and Cognitive Impairment in Patients with Diabetes Mellitus Complicated with Acute Stroke - Mengxian Shu; Chunhui Xiang (Emergency Medicine International)
Objectives. To explore the relationship between peripheral blood microRNA-181c (miR-181c), microRNA-101 (miR-101), and cognitive impairment (CI) in patients with diabetes mellitus (DM) complicated with acute stroke (AS). Methods. A retrospective analysis was performed on 70 patients with DM complicated with AS admitted to the hospital between January 2019 and December 2021. According to presence or absence of CI, they were divided into CI group (41 cases) and non-CI group (29 cases). The clinical characteristics and general data (blood glucose and blood lipid) of patients were statistically analyzed. The relative expression levels of miR-181c and miR-101 in peripheral blood were detected by real-time fluorescence quantitative PCR. The risk factors of CI were analyzed by logistic regression analysis. The diagnostic value of peripheral blood miR-181c and miR-101 for CI was evaluated by receiver operating characteristic (ROC) curves. Results. The relative expression levels of peripheral blood miR-181c and miR-101 in the CI group were lower than those in the non-CI group (P<0.05). The occurrence of CI was related to age, course of DM, AS location, time from onset to admission, HbA1c, TG, UA, and Hcy levels (P<0.05). Logistic regression analysis showed that age, AS location, HbA1c, miR-181c, and miR-101 were related influencing factors of CI in patients with DM complicated with AS (P<0.05). The results of ROC curves analysis showed that AUC, sensitivity, and specificity of miR-181c combined with miR-101 for predicting CI were 0.865, 73.17%, and 89.66%, respectively (P<0.05). Conclusions. The peripheral blood miR-181c and miR-101 are low expressed in patients with DM complicated with AS, and advanced age, intracortical AS lesions, increased HbA1c, and low expression of miR-181c and miR-101 are all independent risk factors for CI in patients with DM complicated with AS. Besides, the combined detection of miR-181c and miR-101 expression has a good diagnostic value for CI.